Enhancement of Bulk Cellulase Enzyme Activity with Variations in Fermentation Conditions and Extraction - Saudalimka, Joevin
The 2nd generation bioethanol is ethanol produced by utilizing agriculture waste. Agriculture waste contains cellulose, a polymer of glucose, which needs to be hydrolyzed prior to its usage as a fermentation substrate for bioethanol production. The enzyme that plays an important role in this hydrolysis process is a cellulase enzyme. The high cost of producing cellulase enzymes is the main obstacle in the production of 2nd generation bioethanol. One of the causes of high-cost-enzyme production is the commercial enzymes which are still produced by Submerged Fermentation (SmF) method. Although SmF method has eased in controlling the operating conditions, the following complex purification process leads to high cost in the downstream processing. An alternative that can be used to overcome this problem is the use of Solid-State Fermentation for cellulase production, which has a simpler downstream process. This study aims to increase the activity of bulk cellulase enzymes produced by the SSF method. Cellulase is produced by using oil palm empty fruit bunch (OPEFB) as C-source, Mandels nutrient, and Trichoderma viride fungi. Fermentation is carried out in 250 ml Erlenmeyer flask. Variations of experiment conducted in this study included variation in glucose concentration (0,003 g, 0,006 g, 0,009 g), Tween 80 concentration (1%, 2%, 3%), and extraction condition (solid to liquid ratio and number of extraction stages). The experimental results showed that cellulase activity can be increased by adding a certain amount of glucose to the fermentation medium and increasing the solid to the liquid ratio for the enzyme extraction process. In contrast, variations in the addition of Tween 80 and the number of extraction stages did not have a significant effect on increment of cellulase activity. In addition, excessive concentration of Tween 80 and glucose in the fermentation medium can lead to a reduction in cellulase activity.